Special Chimeric Antigen Receptor (CAR) Modifications of T Cells: A Review - Miao, Lele; Zhang, Juan; Huang, Binjie; Zhang, Zhengchao; Wang, Song; Tang, Futian; Teng, Muzhou; Li, Yumin (Frontiers in Oncology, 2022)
Chimeric antigen receptor (CAR) -T cell therapy has become one of the hot topics in tumor immunity research in recent years. Although CAR-T cell therapy is highly effective in treating hematological malignancies, there are numerous obstacles that prevent CAR-T cells from having anti-tumor effects. Traditional CARs, from the first to the fourth generation, are incapable of completely overcoming these challenges. Therefore, identifying ways to boost the efficacy of CAR-T cells by utilizing the limited tumor surface antigens has become an urgent area of research. Certain special CARs that have special structures, special systems, or are greatly improved on the basis of traditional CARs, such as tandem CAR, dual-signaling CARs, AND-gate CARs, inhibitory CAR, AND-NOT CARs, CARs with three scFvs, ON/OFF-switch CARs, and universal CARs have been introduced. This study aims to use these special CARs to improve the anti-tumor ability, accuracy, and safety of CAR-T cells. In addition to summarizing various special CARs of T cells, this paper also expounds some of our own conjectures, aiming to provide reference and inspiration for CARs researchers.